PENEGAKKAN UNDANG-UNDANG PILKADA DALAM RANGKA MENCEGAH DAN MENANGGULANGI TINDAK PIDANA POLITIK UANG (MONEY POLITIC) TERKAIT PILKADES SERENTAK 2019 DI DESA MEKAR SALUYU KECAMATAN CIMENYAN KABUPATEN BANDUNG - Musa Darwin Pane; R. Ficry Sukmadiningrat; Maulana Nur Rasyid (Faculty of Law, Universitas Pattimura, 2020)
The general election does not always run smoothly where in some practices there is money politics carried out by prospective leaders by distributing some money to the public with the aim of electing the prospective leader at the time of voting. This research uses the empirical normative legal research method which is a merger of normative legal approaches with the addition of various empirical elements. Normative-empirical research methods regarding the implementation of normative legal provisions (laws) in every particular legal event that occurs in a society. The method of approach in this research uses secondary data consisting of primary legal materials (data obtained directly from people's lives by means of interviews), secondary legal materials and tertiary legal materials. Money politics activities carried out by prospective leaders become a habit in conducting general elections to attract the public so that they vote because most people do not believe or are not affected by the vision and mission and programs presented by the prospective leaders. Money politics has become a recognized practice at various levels of the general elections from the presidential election to the village head due to the lack of strict supervision and enforcement of general elections that should be free, safe, honest, fair, and secret.